IMPLEMENTASI LOGIKA FUZZY UNTUK SISTEM PENDUKUNG KEPUTUSAN (STUDI KASUS DI TOKO KOMPUTER MASCOM SUKOHARJO) - Aditya Dwi Jatmiko; Sri Huning Anwariningsih; Dahlan Susilo (Universitas Sahid Surakarta, 2016)
Mascom computer store is one of the stores that serve to sale and purchase of computers. The process in selling notebook, process there is a problem in the service tothe customer. The officer find difficulty in selling notebook to work customer questions that are ambiguous. Of the handle the problem in answering customer questions uses fuzzy logic. The uses fuzzy logic based on, the concept of fuzzy logic, is easy to understand , very flexible logic , on has the tolerance of unpropriate among other. Inthis final project development system of waterfall method un structure based design is used. Decision support system was made by using Visual Basic 6. This decision support system helps in notebook selling that are ambigious becomes easier to understand for the customer. This result of final project is application that can be used by Mascom in decesing notebook for customer.